Identifying patterns in unplanned hospital admissions during the COVID‐19 pandemic: a single‐centre retrospective study. Issue 6 (21st June 2021) - Goel, Vishal; Chan, R. Kimberley; Smibert, Olivia C.; Holmes, Natasha E.; Marhoon, Nada; Bach, Cindy‐Anne T.; Trubiano, Jason A.; Jones, Nicholas R.
Abstract: Background: Countries with a high prevalence of COVID‐19 have identified a reduction in crude hospital admission rates for non‐COVID‐19 conditions during the pandemic. There remains a paucity of such data from lower prevalence countries, including Australia. Aims: To describe the patterns of unplanned hospital daily admission rates during the COVID‐19 pandemic in a major Australian metropolitan hospital, with a focus on acute medical presentations including acute coronary syndrome (ACS), stroke and falls. Methods: This single‐centre retrospective analysis analysed hospital admission episodes between 1 March and 30 April 2020 (COVID‐19‐era) and compared this to a historical cohort during the same period between 2017 and 2019 (pre‐COVID‐19). Information collected included total admission rates and patient characteristics for ACS, stroke and falls patients. Results: A total of 12 278 unplanned admissions was identified across the study period. The daily admission rate was lower in the COVID‐19‐era compared with pre‐COVID‐19 (46.59 vs 51.56 days, P < 0.001). There was also a reduced average daily admission rate for falls (7.79 vs 9.95 days, P < 0.001); however, similar admission rates for ACS (1.52 vs 1.49 days, P = 0.83) and stroke (1.56 vs 1.76 days, P = 0.33). Conclusions: Public health interventions have been effective in reducing domestic cases of COVID‐19 in Australia. At our tertiary metropolitan hospital, we have observed a significant reduction in unplanned hospital admission rates during the COVID‐19‐era, particularly for falls. Public health messaging needs to focus on educating the public how to seek medical care safely and promptly in the context of the ongoing COVID‐19 crisis.